2013
DOI: 10.1111/ppa.12159
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that nematodes may vector the soft rot‐causing enterobacterial phytopathogens

Abstract: Bacterial soft rot is a globally significant plant disease that causes major losses in the production of many popular crops, such as potato. Little is known about the dispersal and ecology of soft-rot enterobacteria, and few animals have been identified as vectors for these pathogens. This study investigates whether soil-living and bacterial-feeding nematodes could act as vectors for the dispersal of soft-rot enterobacteria to plants. Soft-rot enterobacteria associated with nematodes were quantified and visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The mCherry-labelled Salmonella were seen only internally within the gut of the nematodes, and none was observed on the nematode cuticle. Many bacterial and fungal pathogens interact with nematodes by initially binding to the cuticle (Hodgkin et al, 2000;Nussbaumer et al, 2004;Lee et al, 2011), yet, similar to our finding, no attachment to the cuticle was observed in the case of E. coli and C. elegans (Nykyri et al, 2014). Enteropathogenic bacteria, such as Salmonella, express a wide array of fimbriae and other proteinaceous adhesins that mediate bacterial adherence to host cells and to a range of abiotic surfaces (Jaglic et al, 2014).…”
Section: Presence Of S a L M O N E L L A On Or In A Bu Etsch Liisupporting
confidence: 85%
“…The mCherry-labelled Salmonella were seen only internally within the gut of the nematodes, and none was observed on the nematode cuticle. Many bacterial and fungal pathogens interact with nematodes by initially binding to the cuticle (Hodgkin et al, 2000;Nussbaumer et al, 2004;Lee et al, 2011), yet, similar to our finding, no attachment to the cuticle was observed in the case of E. coli and C. elegans (Nykyri et al, 2014). Enteropathogenic bacteria, such as Salmonella, express a wide array of fimbriae and other proteinaceous adhesins that mediate bacterial adherence to host cells and to a range of abiotic surfaces (Jaglic et al, 2014).…”
Section: Presence Of S a L M O N E L L A On Or In A Bu Etsch Liisupporting
confidence: 85%
“…The SRE are found worldwide and have been isolated from plants of more than half of angiosperm families as well as from soil, rivers, ground waters, insects, molluscs, and nematodes (Perombelon and Kelman, 1980;Perombelon, 2002;Ma et al, 2007;Laurila et al, 2008;Nykyri et al, 2014;Parkinson et al, 2014). They are Gram-stainnegative, rod-shaped, facultative anaerobes that produce a wide range of PCWDE and cause diseases such as blackleg and soft rot.…”
Section: The Enemy -Soft Rot Enterobacteriaceae -D Solanimentioning
confidence: 99%
“…The evidence that soft rot enterobacteria such as Pectobacterium carotovorum colonize nematodes and use them as vectors suggests the importance of nematodeeplant pathogen interaction in plant disease epidemiology (Nykyri et al, 2013). Under field conditions, the bacterial-feeding nematodes may transport bacteria to a relatively short distance, such as between neighboring potato tubers or plants or from unrotten plant remnants to healthy plants in arable land.…”
Section: Existence Of Biotic and Abiotic Associations That Lead To Comentioning
confidence: 99%